Stephen Wall, Trollope and character and other essays on Victorian literature - Perry, Seamus (Anthem nineteenth century studies., 2018)
'Stephen Wall, "Trollope and Character" (1988) and Other Essays on Victorian Literature' is a collection of critical essays by the eminent literary critic Stephen Wall, including his exceptional writings on Anthony Trollope, as well as brilliant studies of Charles Dickens and other major Victorian figures.